The Effect of Transobturator Tape Surgery on Female Sexual Functions: A Systematic Review - Engin Yildirim; Nuriye Buyukkayaci Duman; Umit Gorkem; Ozgur Kan (Gynecology Obstetrics & Reproductive Medicine)
Objective: Stress urinary incontinence is one of the diseases that change the quality of life of women. Although there are various medical and surgical treatment modalities exist, transobturator tape surgery is one of the current options with the least complication rates. The aim of this systematic review was to evaluate sexual functional results after the transobturator tape procedure.